The True Costs of College - Kendall, Nancy; Goerisch, Denise; Kim, Esther C.; Vernon, Franklin; Wolfgram, Matthew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book examines the true costs of attendance faced by low- and moderate-income students on four public college campuses, and the consequences of these costs on students$1 (Bacademic pathways and their social, financial, health, and emotional well-being. The authors$1 (Bexploration of the true costs of academics, living expenses, and student services leads them to conclude that current college policies and practices do not support low-income and otherwise marginalized students$1 (Bwell-being or success. To counter this, they suggest that reform efforts should begin by asking value-based questions about the goals of public higher education, and end by crafting class-responsive policies. They propose three tools that policymakers can use to do this work, and steps that every person can take to revitalize public support for public education, equity-producing policies, and democratic participation in the public arena.s
1. Introduction -- 2. Assumptions about Higher Education and the American Dream -- 3. The True Cost of Academics -- 4. The True Costs of Living Expenses -- 5. The True Costs of Student Fees -- 6. Conclusion -- .
Keywords: Education; Higher education; Educational sociology; Education and state; Education, general; Higher Education; Sociology of Education; Education Policy